Clinical presentation of Long QT Syndrome in a case series study in Iraq - AL-HAMDI, AMAR Talib (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Long QT syndrome is an important cause of arrhythmic death, and it is characterized by electrocardiographic changes and a prolonged QT interval. Patients may present with sudden cardiac death, recurrent syncope, and palpitation.Objective: Clinical orientation for the Long QT syndrome and minimizing its misdiagnosis to achieve high diagnostic index.Patients and Methods: Patients presenting with ventricular arrhythmias, syncope, dizzy spells, and prolonged, non-drug-induced QT interval from 2004 uptil 2019 at Al Nasirya Heart Center , Al Sulaimanya Heart Hospital, and Al Nahrain Teaching Hospital were enrolled in this study. All aptients studied clinically and followed up. Management included beta blocker drug therapy and ICD implantation.Results: Forty-two patients were included within 15 years, comprising 22 pediatric and 20 adult patients (26 males, 16 females). Ventricular fibrillation reported in 18 patients and ventricular tachycardia in five patients. Thirty-eight patients received beta blockers, and 85% showed marked reduction in ventricular arrhythmia events. Implantable cardioverter-defibrillator (ICD) was implanted in 34 patients.The diagnosis of Long QT syndrome was missed in 85% of cases during the provisional medical contacts .Conclusion: In this case series study patients with LQTS presented with syncope, recurrent dizzy spells or palpitation. The diagnosis requires high index of diagnostic suspicion.This case study is intended to orient physicians to diagnosis this fatal problem.